THE IMPORTANT ROLE OF INTELLECTUAL PROPERTY CENTERS IN UNIVERSITIES IN ENCOURAGING THE ESTABLISHMENT OF INTELLECTUAL PROPERTY - Oksidelfa Yanto Yanto (Faculty of Law, Universitas Sebelas Maret, 2020)
This research is purposed to determine the form of obligation of lecturers at universities in producing intellectual property and also to find out how important the role of intellectual property centers in universities is in encouraging the establishment of intellectual property. The research method used is normative juridical with the presentation of data in the form of secondary data which includes primary legal materials, secondary legal materials and tertiary legal materials. The results of the study show that lecturers have a very important role in creating intellectual property, this is because lecturers must continue to develop and disseminate science, technology and art through various research and innovation activities carried out, as a form of implementing the Tri Dharma Perguruan Tinggi (Three Pillars of Higher Education). For the time being, the existence of intellectual property centers at universities can facilitate the management of intellectual property for the academic community. Intellectual Property Centers in Higher Education can foster enthusiasm in producing intellectual works. With the existence of this institutional unit, all academics and even the public will always receive socialization, education in research development and intellectual property-oriented community service.